2021
DOI: 10.1037/amp0000812
|View full text |Cite
|
Sign up to set email alerts
|

Local housing market dynamics predict rapid shifts in cultural openness: A 9-year study across 199 cities.

Abstract: Accumulating evidence suggests that culture changes in response to shifting socioecological conditions; economic development is a particularly potent driver of such change. Previous research has shown that economic development can induce slow but steady cultural changes within large cultural entities (e.g., countries). Here we propose that economically driven culture change can occur rapidly, particularly in smaller cultural entities (e.g., cites). Drawing on work in cultural dynamics, urban economics, and geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Maps of explicit (left) and implicit (right) regional intergroup biases, as reflected in the responses of Project Implicit visitors Note. Maps generated using distance-based weighting (Brenner, 2017;Ebert et al, 2021). Specifically, we used the most fine-grained geographical information available in the data (i.e., visitor's county of residence) and calculated a score for each geographical unit that is based on all observations in the data.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Maps of explicit (left) and implicit (right) regional intergroup biases, as reflected in the responses of Project Implicit visitors Note. Maps generated using distance-based weighting (Brenner, 2017;Ebert et al, 2021). Specifically, we used the most fine-grained geographical information available in the data (i.e., visitor's county of residence) and calculated a score for each geographical unit that is based on all observations in the data.…”
Section: Figurementioning
confidence: 99%
“…(Plant & Devine, 1998), based on the responses of N = 100,262 Project Implicit visitors. Maps were generated using the same distancebased weighting approach as in Figure 1 (Brenner, 2017;Ebert et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…For example, regional variation in the legalization of same sex marriage in the United States led to swift and substantial state-wide differences in implicit and explicit antigay bias (Ofosu, Chambers, Chen, & Hehman, 2019). Likewise, Götz et al (2021) showed that changing amenities in cities (measured by housing prices) lead to swift and substantial changes in city-level openness.…”
Section: The Many Geographical Layersmentioning
confidence: 99%
“…Some of the articles in this special issue focus on the "What" of cultural change-documenting shifts in specific phenomena such as prejudice (Charlesworth & Banaji, 2021), mental health (Infurna et al, 2021), individualism (Hamamura et al, 2021), social mobility (Chan et al, 2021), and religious beliefs and practices (Jackson et al, 2021). Other articles focus on the "Why"-testing theories regarding the causes of specific cultural changes, such as shifts over time in levels of individualism (Kusano & Kemmelmeier, 2021), or openness (Götz et al, 2021), or fertility (Rotella et al, 2021). Finally, the special issue includes articles that tackle the "How"-attempts to model and capture the broad processes involved in cultural change writ large.…”
mentioning
confidence: 99%
“…These pieces capture a range of theoretical perspectives that have been brought to bear on how and why cultures change over time, including insights from evolutionary psychology (Jackson et al, 2021; Kusano & Kemmelmeier, 2021; Pan et al, 2021), behavioral ecology (Rotella et al, 2021), cultural evolution (Schaller & Muthukrishna, 2021), and socioecological psychology (Buttrick & Oishi, 2021). The special issue also highlights the diversity of methodological approaches in this emerging field ranging from computational modeling (Jung et al, 2021; Schaller & Muthukrishna, 2021; Pan et al, 2021), to machine learning (Sheetal & Savani, 2021; Stavrova et al, 2021), to time series analyses (Charlesworth & Banaji, 2021; Chan et al, 2021; Götz et al, 2021; Kusano & Kemmelmeier, 2021; Rotella et al, 2021).…”
mentioning
confidence: 99%